Faktor-faktor yang Berhubungan dengan Intensi Pencarian Bantuan Kesehatan Mental pada Mahasiswa Sarjana FKM UI - Muhammad Ma'shum; Caroline Endah Wuryaningsih; Dien Anshari (Jurnal Medika Hutama, 2025)
University students are vulnerable to mental health problems such as anxiety and depression. However, there is still limited research examining factors associated with mental health help-seeking among educated populations. This study aims to identify factors associated with the intention to seek mental health help among undergraduate students at the Faculty of Public Health, Universitas Indonesia (FKM UI). This quantitative study employed a cross-sectional design with quota sampling (n=108). The dependent variable was intention to seek help from mental health professionals, while the independent variables were attitudes toward help-seeking, subjective norms, and perceived behavioral control. Univariate analysis showed the mean score for intention was 2.64 (SD=0.53). The mean scores for attitudes toward behavior, subjective norms, and perceived behavioral control were 3.22 (SD = 0.47), 2.91 (SD = 0.4), and 2.88 (SD = 0.41), respectively. Spearman’s correlation test results showed that only perceived behavioral control was positively associated with help-seeking intention (p < 0.001), while attitudes and subjective norms were not associated with intention (p = 0.094 and p = 0.284). Based on these findings, health promotion efforts to improve mental health help-seeking among FKM UI undergraduate students should place greater emphasis on strengthening perceived behavioral control.